2016
DOI: 10.18632/oncotarget.14356
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant effect of recombinant NT4-NAP/AAV on social isolated mice through intranasal route

Abstract: The purpose of the present study was to observe the depression-like behavior induced by social isolation; detect the antidepressant effect of a recombinant adeno-associated virus (AAV) expressing NAP on social isolation mice by intranasal delivery. After construction of NT4-NAP/AAV, expression of NAP was confirmed in vitro. 3-week-old C57/BL mice were bred individually in cages as social isolation-rearing. Six weeks later, the first subset of mice underwent behavioral tests and western blot; the second was for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Brain issues were first weighed, then added normal saline according to a certain proportion (1 mg: 25 μl), homogenized by Soniprep (BioSpec Products, Inc., Bartlesville, USA), and supernatants were extracted after centrifugation. NMDAR1 and D2R levels were measured using a mouse enzyme-linked immuno-sorbent assay (ELISA) Kit (Shanghai Hushang Biotechnology, Shanghai, China) following standard procedures described in a previous study 15 . First, the prepared sample and the standard were placed in separate plate wells and incubated for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Brain issues were first weighed, then added normal saline according to a certain proportion (1 mg: 25 μl), homogenized by Soniprep (BioSpec Products, Inc., Bartlesville, USA), and supernatants were extracted after centrifugation. NMDAR1 and D2R levels were measured using a mouse enzyme-linked immuno-sorbent assay (ELISA) Kit (Shanghai Hushang Biotechnology, Shanghai, China) following standard procedures described in a previous study 15 . First, the prepared sample and the standard were placed in separate plate wells and incubated for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, NAP treatment prevents neuronal death often seen with clozapine, a commonly used anti-psychotic drug for treatment of schizophrenia (Merenlender–Wagner et al, 2014 ). Moreover, NAP reduces depressive-like behavior in mice following social isolation, exemplified by reduced immobility in the forced swim test and reduced anhedonic phenotype (Liu et al, 2017 ). NAP administration in DISC1 knockout mice, a model for schizophrenia, reduces anxiety levels in the elevated plus maze.…”
Section: Potential Benefit Of Nap For Treatment Of Psychiatric and Nementioning
confidence: 99%
“…Accumulating evidence has shown that BDNF is implicated in the pathophysiology of depression and the antidepressant effects of exercise (Heyman et al, 2012;Archer et al, 2014;Lu et al, 2014). In addition, previous studies have suggested that neurotrophins such as NGF, NT-3, and NT-4/5 are important factors for neuroplasticity regulation, which have an important role in the neurotrophic hypothesis of antidepression (Pae et al, 2008;Overstreet et al, 2010;Hochstrasser et al, 2013;Lang and Borgwardt, 2013;Liu et al, 2017). The aim of this study was to examine the association between the neurotrophins and the antidepressant action of exercise intervention during METH abstinence.…”
Section: Introductionmentioning
confidence: 99%